Prevalence and Factors Associated with Raw Freshwater Fish Consumption among Populations in Areas at Risk of Liver Fluke Disease - Sonthon, Paithoon; Janma, Narumon (Journal of Bamrasnaradura Infectious Diseases Institute, 2026)
This study aimed to determine the prevalence and examine factors associated with raw freshwater fish consumption among populations at risk of liver fluke infection, most of whom were migrants from the northeastern region of Thailand. An analytical cross-sectional study was conducted among residents of Khok Prong Subdistrict, Wichian Buri District, Phetchabun Province. A total of 1,868 participants were recruited using a multistage sampling technique. Data were collected using a structured questionnaire and analyzed using multiple logistic regression to estimate adjusted odds ratios (AORs) with 95% confidence intervals (95% CI), with statistical significance set at 0.05. The overall prevalence of raw freshwater fish consumption was 89.03%. Significant factors associated with consumption included age 31–45 years (AOR = 2.63; 95%CI: 1.53–4.58), lower educational attainment (primary: AOR = 4.77; 95%CI: 2.79–8.11; lower secondary: AOR = 4.89; 95%CI: 2.64–9.23; upper secondary: AOR = 2.82; 95%CI: 1.51–5.07), alcohol consumption (AOR = 1.73; 95%CI: 1.16–2.64), and residence within 1 kilometer of a water source (AOR = 1.43; 95%CI: 1.01–2.00). In contrast, regular exposure to liver fluke-related information (AOR = 0.64; 95%CI: 0.41–0.98) and higher levels of disease-related belief (AOR = 0.55; 95%CI: 0.33–0.87) were protective factors. This study demonstrated a high prevalence of raw freshwater fish consumption in at-risk populations, with significant associations observed for age, educational level, alcohol consumption, and proximity to water sources. Regular exposure to health information and accurate disease-related beliefs were identified as protective factors. These findings highlight the need to integrate liver fluke prevention into routine health screening programs, alongside context-specific behavioral interventions targeting high-risk groups through interactive communication strategies to address misconceptions and promote safer practices.